ANALISIS PENERAPAN GRI STANDAR 404, BIAYA RATARATA PELATIHAN DAN RASIO PENGELUARAN BIAYA KUALITAS PELATIHAN DAN PENDIDIKAN TERHADAP TOTAL BIAYA OPERASIONAL LAINNYA PADA BANK BUMN - Oktris, Lin; Ahadiyat, Kiki Kusumayadi (School of Accountancy, University of Agung Podomoro, 2022)
This study conducted to analize the application of GRI Standards 404 on Government OwnedBanks in Indonesia (Bank Mandiri, BRI, BNI and BTN), the average trainingand educational costfor employee, and the ratio of total training and educational cost (as a part of quality cost) to totalother operating cost in each Government Owned Banks. The data used are secondary data, obtainedfrom official website of each banks. Sustainability Reporting and Financial Report for the year of 2020are the basic data used for this study. This study is a case study. This study shows that all ofGovernment Owned Banks are conforms to GRI Standards 404 about employee’s training andeducation. They are spending a substantial amount of training and education cost on 2020, but theratio of training and education cost to total other operating cost are unsubstantial.